2021
DOI: 10.1002/jgh3.12502
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab in Crohn's disease: Real‐world outcomes from the Sicilian network for inflammatory bowel diseases

Abstract: Background and Aim Ustekinumab is approved in Europe for the treatment of moderate to severe Crohn's disease (CD). Italian real‐life data are scarce, so the aim of this study was to assess the effectiveness and safety of ustekinumab in an Italian cohort of CD patients. Methods Data of patients with CD who started using ustekinumab were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease. Primary end‐points were steroid‐free clinical remission at 8, 24, and 52 weeks of therapy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…More recently, results from a Sicilian CD cohort were published with a total of 131 patients. Steroid-free clinical remission rates at 24 and 52 weeks of follow-up were 40% (47/117) and 43% (33/76) [12] .…”
Section: Discussionmentioning
confidence: 94%
“…More recently, results from a Sicilian CD cohort were published with a total of 131 patients. Steroid-free clinical remission rates at 24 and 52 weeks of follow-up were 40% (47/117) and 43% (33/76) [12] .…”
Section: Discussionmentioning
confidence: 94%
“…The Sicilian Network for IBD has recently published prospectively collected data for 131 patients with CD who were treated with ustekinumab. 24 Almost all patients (99%) had been previously treated with biologic therapy. At week 8, corticosteroid-free clinical remission was achieved in 35% of the patients, which was similar to the rate obtained in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several real-world studies have confirmed the effectiveness and safety of ustekinumab in patients with CD after failure of or intolerance to anti-TNF-α therapy. 13 31 However, very few data concerning the Italian real-life experience using ustekinumab for the treatment of CD have been reported. 22 , 24 Moreover, because of the relatively recent regulatory approval of ustekinumab, some studies either did not include the intravenous (IV) induction regimen or evaluated patients for short periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, clinically relevant information about IMIDs (e.g., disease severity) was missing from the network of regional claims databases. Nevertheless, one of the ambitious goals of the VALORE project is to enrich claims data with clinically relevant information such as disease activity scores, exact indication of use, and reasons for treatment discontinuation through linkage with population-based disease registries from the same catchment area, which are available in some Italian regions [ 52 54 ]. For this scope, exploratory analyses have been conducted in the last year to link regional claims data with the Sicilian registry of biological drug users with inflammatory bowel disease and will be conducted in the near future with Veneto registries of biological drugs users with dermatology, rheumatology, or gastroenterology diseases.…”
Section: Discussionmentioning
confidence: 99%